Good offices: a veritable alternative dispute resolution tool for peace and nation building (2023)
Disputes are a part of life for living creatures, from insects to human beings. While insects or animals mayfightfor space, territory and dominance, human beings and countries fight each other for territory and may engage in war. Throughout history, differences resulting in conflict were resolved, are still being resolved and will continue to be resolved. The traditional societies settled and still settle family disputes without interference from and invitation to the third parties who are not members of that family. The dominance of the British through colonization introduced cultures hitherto unknown into many societies. This also included a justice system foreign to the people. Litigation was one of such. The taking of a dispute out of the family or community jurisdiction, to a court that is set up by the state was introduced and adopted. Litigation was adopted as a process with its advantages and disadvantages. The disadvantages and the problems in litigation brought about a search for an alternative. These alternatives are not totally free of problems but are more acceptable in respect to certain types of cases, than litigation. It is therefore an alternative to litigation. People who have a common identity tend to stay together to build unified societies and nations. However, there are situations that may make it difficult or impossible for people to stay together. In such situations, if actions are not promptly taken to resolve the issues, there may be conflict. This paper looks at the concepts of conflict and conflict resolution, peace in the midst of conflict and the efforts that are made at nation building. The paper, through the use of case studies to support a preposition, suggests that the use of alternatives dispute resolution (ADR) methods in some cases, through the establishment of a grounded ADR structure in place, to resolve conflict rather than the use of litigation may be a solution to nation building.